Cytochrome b mitochondrial DNA characteristic from non-invasive samples of wild population Javan Banteng (Bos javanicus d’Alton, 1823) - MARYATUL QIPTIYAH; SATYAWAN PUDYATMOKO; AYPBC WIDYATMOKO; MUHAMMAD ALI IMRON; ILG NURTJAHJANINGSIH (Society for Indonesian Biodiversity, 2019)
Qiptiyah M, Pudyatmoko S, Widyatmoko AYPBC, Nurtjahjaningsih ILG, Imron MA. 2019. Cytochrome-b mitochondrial DNA characteristic from non-invasive samples of wild population Javan Banteng (Bos javanicus d’Alton, 1823). Biodiversitas 20: 350-355. Javan banteng (Bos javanicus javanicus) is one of the protected big mammals in Indonesia, due to its population decline. The main populations of Javan banteng are currently in Ujung Kulon National Park (UKNP), Alas Purwo National Park (APNP), Meru Betiri National Park (MBNP) and Baluran National Park (BNP). These four remaining populations are fragmented with wide geographical distances. Population reduction and fragmentation between populations can promote depletion of genetic characters. This study aim to examine the genetic characteristics of Javan banteng based on cytochrome b region of mitochondrial DNA. Genetic materials were obtained by a non-invasive method (feces) from four national parks in Java.The sequencing results were aligned with cytochrome b mitochondrial DNA sequences from the other banteng (B. j. lowi and B. j. birmanicus) from the GeneBank sequence database. The results from this study revealed that the genetic distance of Javan banteng between UKNP, APNP, and BNP were 0, while the genetic distance between these populations with MBNP was 0.005. Moreover, the population of MBNP has only one haplotype that does not exist in the other populations. Based on these results, there should be caution in conducting genetic infusion of Javan banteng in their natural populations, especially in Meru Betiri National Park.